Pengaruh Akuntabilitas, Transparansi dan Partisipasi Masyarakat terhadap Pengelolaan Dana Desa: Studi Empiris pada Nagari di Kabupaten Tanah Datar - Moudiana Fahisa; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the effect of accountability, transparency and community participation on the management of village funds (Empirical Study on Nagari in Tanah Datar Regency). The population used in this study were 75 nagari in Tanah Datar Regency, totaling 600 nagari apparatus. The sampling technique used purposive sampling method. In determining the number of samples using the Issac and Michael formulas, 234 nagari apparatus were obtained. This type of research is quantitative research. The source of data in this study is primary data by distributing questionnaires to village officials in Tanah Datar Regency. Data analysis used multiple linear regression analysis. The results of this study indicate that accountability, transparency and community participation have a positive and significant effect on the management of village funds.